Oral and Inhaled Fosamprenavir Reverses Pepsin‐Induced Damage in a Laryngopharyngeal Reflux Mouse Model. (9th June 2022) - Johnston, Nikki; Samuels, Tina L.; Goetz, Christopher J.; Arnold, Leggy A.; Smith, Brian C.; Seabloom, Donna; Wuertz, Beverly; Ondrey, Frank; Wiedmann, Timothy S.; Vuksanovic, Nemanja; Silvaggi, Nicholas R.; MacKinnon, Alexander C.; et al.
Abstract : Objective: More than 20% of the US population suffers from laryngopharyngeal reflux. Although dietary/lifestyle modifications and alginates provide benefit to some, there is no gold standard medical therapy. Increasing evidence suggests that pepsin is partly, if not wholly, responsible for damage and inflammation caused by laryngopharyngeal reflux. A treatment specifically targeting pepsin would be amenable to local, inhaled delivery, and could prove effective for endoscopic signs and symptoms associated with nonacid reflux. The aim herein was to identify small molecule inhibitors of pepsin and test their efficacy to prevent pepsin‐mediated laryngeal damage in vivo. Methods: Drug and pepsin binding and inhibition were screened by high‐throughput assays and crystallography. A mouse model of laryngopharyngeal reflux (mechanical laryngeal injury once weekly for 2 weeks and pH 7 solvent/pepsin instillation 3 days/week for 4 weeks) was provided inhibitor by gavage or aerosol (fosamprenavir or darunavir; 5 days/week for 4 weeks; n  = 3). Larynges were collected for histopathologic analysis. Results: HIV protease inhibitors amprenavir, ritonavir, saquinavir, and darunavir bound and inhibited pepsin with IC50 in the low micromolar range. Gavage and aerosol fosamprenavir prevented pepsin‐mediated laryngeal damage (i.e., reactive epithelia, increased intraepithelial inflammatory cells, and cell apoptosis). Darunavir gavage elicited mild reactivity and no discernable protection; aerosol protected against apoptosis. Conclusions: Fosamprenavir and darunavir, FDA‐approved therapies for HIV/AIDS, bind and inhibit pepsin, abrogating pepsin‐mediated laryngeal damage in a laryngopharyngeal reflux mouse model. These drugs target a foreign virus, making them ideal to repurpose. Reformulation for local inhaled delivery could further improve outcomes and limit side effects. Level of evidence: NA. Laryngoscope, 133:S1–S11, 2023 Abstract : Compelling evidence highlights a major role for pepsin (independent of gastric acid) in reflux‐attributed laryngeal symptoms and endoscopic findings refractory to PPI therapy. Herein, fosamprenavir, and darunavir, FDA‐approved retroviral therapies for HIV/AIDS, bound and inhibited pepsin, abrogating pepsin‐mediated laryngeal inflammation and mucosal damage in an LPR mouse model. These drugs target a foreign virus so are ideal to repurpose. Reformulation for local inhaled delivery could further improve outcomes and limit side effects.